ASSOCIATION BETWEEN THE DEGREE OF SKIN FIBROSIS AND CLINICAL-LABORATORY INDICATORS IN SYSTEMIC SCLEROSIS (International Conference on Modern Science and Scientific Studies, 2025)
Skin fibrosis is a hallmark of systemic sclerosis and serves as a clinical indicator of disease severity. The modified Rodnan skin score (mRSS) is a validated tool to quantify skin involvement. Correlating skin fibrosis severity with laboratory markers such as erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and antinuclear antibodies (ANA) can enhance disease monitoring and prognostication.